Serum Levels of Thyroid Hormones in Infertile and Fertile Women Attending a Tertiary Care Hospital in North-Central Nigeria: A Comparative Reproductive Medicine Study (American Journal of Medical Science and Innovation, 2023)
Thyroid hormones have profound effects on reproduction. Normal thyroid function is necessary to maintain reproductive physiology, but its functional abnormalities may cause infertility manifesting as menstrual cycle irregularities. Aim of this research was to determine the serum levels of thyroid hormones in infertile and fertile women attending a tertiary care hospital in North-Central Nigeria. This comparative, reproductive medicine, cross-sectional study was carried out among one hundred and six (106) women attending the Gynecology Clinic of the Department of Obstetrics and Gynecology and the Family Planning Clinic of a tertiary care hospital in North-Central Nigeria. Women with a history suggestive of either primary or secondary infertility and the control women with no history of infertility were evenly grouped. Venous blood samples were collected and analyzed using Enzyme-Linked Immunosorbent Assay (ELISA) technique to determine fT3, fT4 and TSH levels. Data obtained were entered and analyzed using Statistical Package for Social Sciences (SPSS) version 23, and the level of statistical significance was set at p